PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI PERUBAHAN SIFAT BENDA - Listiorini, Anisa; Jayadinata, Asep Kurnia; Isrok'atun, Isrok'atun (Jurnal Pena Ilmiah, 2017)
The background of the research in the 5th grade of Primary School Randegan Wetan 1 is the discovery of the fact that the results of student learning on the material changes in the nature of the object is still low. This is because the material obtained by students is less meaningful. To overcome these problems it will be applied Contextual Teaching and Learning(CTL) model. The method used in this research is classroom action research. The subjects in this study were 5th graders of Randegan Wetan 1 Primary School, which amounted to 30 students. The purpose of this study is to improve student learning outcomes on material changes in the properties of objects. This research process is done for three cycles because result learn student reach target at cyle III with percentage 87%. In this case it can be concluded that Contextual Teaching and Learning (CTL) model can improve student learning outcomes